Mutamenti delle democrazie europee contemporanee I casi della Francia e dell'Italia - Lazar, Marc (Lectio Magistralis, 2019)
This volume, on the basis of France and Italy's cases, analyses the changes in party systems and, more generally, in our democracies. The author underlines how it is possible to glimpse the personalization and mediatisation of politics in the appearance of personal and personalised parties; he also studies the rise of populists imposing their themes, language and way of doing politics. The populist style spreads within society and the public space so intensively that the people fighting the populists at the lowest level, in the end, resume their opponents' style. As Ilvo Diamanti wrote: there is now a people-ocracyor a dynamic which is currently destabilising our democracies.